Language Politeness In Directive Speech Acts In The Dialogue Of Youth In Blang Naleung Mameh Village - Humaira, Husina; Safrita , Kamalia; Yanti , Fifi Safrima (JETLEE: Journal of English Language Teaching, Linguistics, and Literature, 2022)
The purpose of this research are (1) define language politeness in directive speech acts in youth dialogue in Blang Naleung Mameh Village and (2) define types of language politeness in directive speech acts in Blang Naleung Mameh village youth dialogue. This research used a qualitative approach. The type of research is descriptive. The research location is in Blang Naleung Mameh Village. The data of this research is in the form of directive speech acts for adolescents in Blang Naleung Mameh Village. The data sources for this study were 22 youths in the Blang Naleung Mameh Village. Based on the results of the data research, it is concluded that there are three types of maxims, namely wisdom, consensus, and sympathy. There are three politeness scales, including the gain and loss scale, the preference scale, and the indirectness scale. Furthermore, there are six types of directive speech acts and their functions, namely (1) request speech acts with the functions of asking, pleading, and inviting; (2) questioning directive speech acts with the functions of asking and interrogating; (3) command directive speech acts with the functions of instructing, ordering, and requiring; (4) prohibitive directive speech acts with the functions of prohibiting and limiting; (5) the directive speech act of granting permission with the function of approving and allowing; and (6) speech acts of advice with the functions of warning, advising, suggesting, and recommending. The dominant directive speech act is the question directive speech act.